Underfunded Modernization: Tobacco Producers and Agricultural Policy in Interwar Greece. - Carmona-Zabala, Juan (Johns Hopkins University Press, 2021)
In this article, I analyze the state-led project of optimizing tobacco production in interwar Greece, as well as its effects on the peasant population. I look at one specific stage within the productive chain, known as primary processing. The history of primary processing allows us to appreciate the interplay of four factors that, I argue, most decisively determined the trajectory of Greece's agricultural policy in the interwar period. Such factors are a) the undercapitalization of the Greek rural economy, b) the ever increasing dependence of the Greek tobacco sector on the German sales market; c) the nonexistence of strong, autonomous agrarian organizations, and d) the pro-merchant stance of successive Greek governments. The scale of analysis proposed in this article can enrich the existing historiography on Greek agriculture by overcoming some of the limitations of the approaches that emphasize quantitative data on productivity, output and land use.
Política de acceso abierto tomada de: https://beta.sherpa.ac.uk/id/publication/8591
Keywords: Tabaco - Cultivo - Grecia; Agricultura - Innovaciones tecnológicas; Agricultura - Grecia - 1918-1939; Grecia; Entreguerras; Agricultura; Tabaco; Modernización